PENGARUH PERMAINAN CONGKLAK TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 4-5 TAHUN DI KB NURUL MA`RIFAH KEC. KALISAT TAHUN AJARAN 2024/2025 - Mutia Fajar Rianti; Mahendra Aswit Sandra Barata; Nury Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Playgroup education is a form of early childhood education that plays a crucial role in developing children's personalities and preparing them for the next level of education. Numeracy is a crucial foundation for early childhood development as a preparation for entering the next level of education. Based on observations, researchers found similar findings to the statement above. Students aged 4-5 at the Nurul Ma'rifah Kindergarten tend not to be able to count objects accurately. Early childhood is not yet able to understand abstract mathematical concepts, so it requires a numeracy learning approach that is appropriate to the child's developmental stage. According to Romlah in Riyenil and Agus (2019: 55), play is a way of learning that provides a feeling of happiness and enjoyment because through play, children can learn about something without having to study it. In the modern era, traditional games are starting to be marginalized by digital games, even though traditional games have benefits that are no less important, including in the aspect of counting. The population in this study were Early Childhood Children (both boys and girls) KB Nurul Ma`rifah in Kalisat District. While the sample in this study were all students in class A with an age range of 4-5 years. This study is a quasi-experimental study, where according to Ruseffendi in Lisa (2019) in a quasi-experiment the sample is not randomly selected subjects but samples are taken randomly class with existing subjects. This study also uses a pretest and posttest design where in this design there are two groups selected randomly Data Analysis in this study uses descriptive statistical analysis and statistical tests (T Test) to see the effect of congklak games on children's counting abilities. The purpose of this study is to provide information to readers regarding the effect of congklak games on counting abilities in early childhood.